ARCHITECTURE EDUCATION IN INDIA: AN ANALYTICAL STUDY OF CURRICULUM AND ITS ALIGNMENT WITH MODERN-DAY DEMANDS - Purohit, Abhay Vinayak; Roy, Madhumita (International Journal of Research -GRANTHAALAYAH, 2025)
By critically examining the current architecture curriculum in India, this study aspires to determine the relevance of education in addressing the demands of an evolving profession. To analyze these aspects and their relevance to modern day, the study investigates the overarching framework provided by regulatory control and implementation by academic institutions, focusing on the curriculum structure, content, and pedagogical methods employed in architectural education to determine the incorporation of contemporary themes such as sustainability, technological integration, and interdisciplinary collaboration. A total of 100 people, including students, educators, and experts, were surveyed using a structured questionnaire. The results indicate that there exist critical disconnects between an existing curriculum and the applied tasks of contemporary architecture, suggesting a need for curricular change. It calls for a proactive, practice-related approach that integrates trends and standards with global perspectives on preparing our graduates within the sphere of built environment challenges.